MOSQUES AS CENTERS OF WORSHIP AND MORAL EMPOWERMENT: A CASE STUDY OF DARUL HUDA MOSQUE, PATTANI - Subaidi, Subaidi; Sukarman, Sukarman; Khoiruddin, Muhammad; Roosdhani, Mohamad Rifqi; Kalupae, Abdulaziz; Tehhaee, Ibrahim; Felo, Noorsafuan Bin Che Noh (Jurnal Al-Ijtimaiyyah, 2025)
This study uses a qualitative approach with a case study method to explore the role of the Darul Huda Mosque in Pattani, Thailand as a place of worship and a means of strengthening the morals of Muslims. Data was collected through participatory observation, in-depth interviews with mosque administrators and congregants, and documentation of religious activities at the mosque. The results show that the mosque is not only a center for obligatory worship such as congregational prayers and Friday prayers, but also functions as a space for spiritual and moral guidance through additional activities such as i'tikaf, wirid, dzikir, and special prayers. The strengthening of the community's morals is realized through solemn sermons and regular recitation activities. This study confirms that the Darul Huda Mosque plays a vital role in shaping the character and strengthening the moral values of Muslims in the social and religious context of the Pattani region.